Band-Suppressed Restoration of X-Ray Images Blurred by Body Movement - Hori, J.; Saitoh, Y.; Kiryu, T.; Okamoto, K.; Sakai, K. (Methods of Information in Medicine, 2000)
The restoration of X-ray images that have been blurred due to body movement are discussed. The observation system for these images is described using a mathematical model, and several restoration filters composed of a series of such models are proposed. These filters restore band-suppressed approximations of the original images. In addition, redundancy is introduced into these restoration filters in order to suppress additive noise. These filters are expanded to be applicable not only to parallel translations, but also to rotations by coordinate transformation. The proposed methods are applied to blurred X-ray images of a bone model of the elbow joint. The parameters of the restoration filter are estimated using a marker attached to the subject as a reference signal.
Keywords: X-Ray Images; Restoration; Band Suppression; Blur; Body Movement